TIPOLOGI PEMANFAATAN RUANG JALAN STUDY KASUS CITY WALK JALAN SLAMET RIYADI SURAKARTA - , TRI HARTANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Since 2007, Surakarta City built area for pedestrians or pedestrian track that was usually called as City Walk. City walk is an open public space which based on the thinking to promote Surakartaâs potential which is exist and grow with the slogan â solo past as solo futureâ. City walk area was designed as green track which is the implementation of city governmentâs attention toward global warming issue. Recently the condition of city walk is excessively used for PKL activities, vehicle parking, pedicap activities, and motor cycle circulation. Therefore this research is very important to know: (a) types of space utilization on city walk, and (b) what factors influencing space utilization of city walk are. Research method used in this research is qualitative method, because the variables influencing this research are qualitative variables. Analysis method to describe the phenomena happen in this research area is done by grounded theory. By the procedure/ steps of coding techniques such as open coding, axial coding and selective coding to analyze variation data appropriately to the phenomena happened in the city walk Surakarta. The result of this study finds that there are eight types/forms space utilization city walk on Slamet Riyadi Street Surakarta. The types of activities on space utilization are influenced by physical and time setting. Besides wide pedestrian track with flat surface and there are street furniture, factors influencing is the existence of building and shaded of vegetations, and function characteristics. Building with commercial function has higher number in activities than noncommercial function. Trees with big stalk and wide branch tend to make calm space under it. The higher levels of activities are the more space utilization.